Role of Younas Qayasi in Evolution of Drama on Peshawar Television - Raj Muhammad Dr.Tahseen Bibi (دریافت)
Drama is a literary genre of fiction .It has dated back as the human history itself. It passed through various cultural boundaries. In Hindustan, various dramatists exhibited their skills and potential in it. When partition of Pakistan took place, the dramatists of KPK, especially showed great contributions. One of among them, Younas Qayasi is well known dramatist, who presented and staged not only Urdu but Pashto and Hindko dramas too. He earned great fame and name at national and International level.